Politik Hukum Dalam Penentuan Batas Usia Capres Dan Cawapres Di Indonesia Perspektif Fiqh Siyasah - Prayoga, Susilo Hadi (El-Dusturie, 2024)
The determination of the age limit for presidential and vice-presidential candidates in Indonesia has sparked political and legal dynamics, particularly regarding the involvement of younger generations in national leadership. This issue surfaced with the nomination of Gibran Rakabuming Raka as a vice-presidential candidate in the 2024 election, influenced by Constitutional Court Decision No. 90/PUU-XXI/2023, which regulates the minimum age requirement for presidential and vice-presidential candidates. Research Question: This article examines how the age requirements for presidential and vice-presidential candidates are viewed from the perspective of Fiqh Siyasah and the political-legal implications in Indonesia. The primary questions include: how does Fiqh Siyasah address these age restrictions, and what are the political and legal implications of the Constitutional Court’s decision within the context of Indonesian democracy? Research Method: This research employs a qualitative approach with a normative legal perspective, analyzing data based on legal documents, court rulings, and relevant literature on Fiqh Siyasah. Data and Findings: The Constitutional Court Decision No. 90/PUU-XXI/2023 amended Article 169 letter q of the Election Law, previously setting the minimum age for presidential and vice-presidential candidates at 40 years, to include an alternative requirement of experience as an elected official. This decision has sparked debate about dynastic politics and the constitutional rights of younger generations. However, it is considered consistent with the principles of Fiqh Siyasah, prioritizing public interest, provided that it aligns with the criteria of good leadership. The findings suggest that this decision does not violate the principles of Fiqh Siyasah; instead, it opens opportunities for younger generations to participate in national leadership in accordance with public welfare and constitutional rights. Keywords: Age Limit, Fiqh Siyasah, Legal Politics.